ANALISIS MOTIVASI BELAJAR SISWA SELAMA PANDEMI COVID-19 DI LINGKUNGAN I KELURAHAN PASAR BATU GERIGIS KECAMATAN BARUS - Meri Santika Pinayungan; Mhd. Nau Ritonga; Roslian Lubis (JURNAL MathEdu (Mathematic Education Journal), 2022)
The background of this research is Covid- 19 pandemic in world that caused global health crisis. This problem made a policy to change offline learning to online. Based on the situation, the researcher is interested to describe the students learning motivation of Junior High School in Lingkungan I Pasar Batu Gerigis, Barus sub-district. The approach of this research used qualitative descriptive and subject of the research is students of SMP in Lingkungan I Kelurahan Padang Masiang. Triangulation sources were used in checking data validity. Questionnaire and interview were used in collecting the data. The result of questionnaire shows 50% in poor motivation, 30% in enough motivation, and 20% in good motivation. Furthermore, the results of interview of students (1) poor motivation because students feel boring, lazy, and incomprehension of the subject, (2) enough motivation because students repeat the subject again and they like environment because they have a lot of friends, (3) good motivation because they are not boring in learning mathematics and the y always do their homework. Based on interview of teacher, She says that students have poor motivation.